Insensitivity of Water-Oxidation and Photosystem II Activity in Tomato to Chilling Temperatures - Martin, Bjorn (1982)
Chilling tomato plants (Lycopersicon esculentum Mill. cv. Rutgers and cv. Floramerica) in the dark resulted in a sizable inhibition in the rate of light- and CO(2)-saturated photosynthesis. However, at low light intensity, the inhibition disappeared and the absolute quantum yield of CO(2) reduction was diminished only slightly. The quantum yield of photosystem II (PSII) electron flow was 18% lower when measured in chloroplasts isolated from chilled leaves than in chloroplasts isolated from unchilled leaves. Even though the maximum rate of PSII turnover in these chloroplasts was 12% lower subsequent to chilling, it was in all cases two or more times that required to support the light- and CO(2)-saturated rate of photosynthesis measured in the attached leaf. The concentration of active PSII centers in chloroplasts isolated from leaves either before or after chilling was determined by measurement of the products of water oxidation from a series of saturating flashes short enough to turnover the electron transport carriers only a single time. There was no significant change in the concentration of active PSII centers due to dark chilling. It was concluded that PSII activity and water oxidation capacity are not significantly impaired in tomato by chilling in the dark and therefore are not primary aspects of the inhibition of CO(2) reduction observed in attached leaves.